PENERAPAN METODE TALAQQI UNTUK MENINGKATKAN BACAAN AL-QUR'AN PESERTA DIDIK MTS DI KABUPATEN BEKASI - Shofiyyah, Shofiyyah; Nurfaiza, Najwa; Sumayyah, Amallia (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
Proficiency in reading the Qur'an according to tajwid rules is an essential competence that must be mastered by students of Islamic Junior High School (Madrasah Tsanawiyah). However, the reality of learning indicates that students' Qur'anic reading proficiency remains suboptimal, particularly in the aspects of makhārijul ḥurūf (articulation points of letters) and the application of tajwid laws. This study aims to improve the quality of students' Qur'anic reading through the implementation of the talaqqi method using a Classroom Action Research (CAR) approach. This study employed a collaborative CAR design conducted in two cycles, comprising the stages of planning, acting, observing, and reflecting. The subjects were 7th-grade students of a Madrasah Tsanawiyah in Bekasi Regency. Data collection techniques included practical Qur'anic reading tests, observation of student activities, interviews, and documentation. The assessment instrument utilized an analytic rubric covering the aspects of makhārijul ḥurūf, ahkām al-tajwīd, and reading fluency. Data were analyzed quantitatively and qualitatively. The results indicated that the implementation of the talaqqi method significantly improved the quality of students' Qur'anic reading. Classical mastery learning increased from 30% in the pre-cycle to 50% in Cycle I, and reached 80% in Cycle II, with the class average score increasing from 76.8 to 81.8. These findings demonstrate that the talaqqi method is effective in correcting recurring reading errors through direct correction and intensive guidance. Thus, the talaqqi method serves as a strategic learning alternative to enhance the Qur'anic reading competence of Madrasah Tsanawiyah students